Graves, beads, and trade in Northwest Argentina: a first ED-XRF characterization of very well-formed objects - María M. Sampietro Vattuone; Susana Martínez Stagnaro; Rosario García Giménez; José L. Peña Monné; Jimena Roldán; Mario G. Maldonado (Arqueología, 1970)
The Tafi Valley has a deep-rooted archaeological research tradition in Northwest Argentina. Most the archaeological settlements are from the Formative Period (500 BC – 1000 AC), these have been studied from several perspectives. This article presents the results of non-destructive ED-XRF analyses on exceptionally manufactured beads dating to 1560 ± 35 BP, recovered from a grave located within a Formative residential unit. The beads were made from chrysocolla, variscite, and turquoise, all of which are foreign materials in the valley. These results indicate that the Tafí Valley was part of the caravan trade route across Northwest Argentina, representing part of the eastern limits of this circulation pattern for the early Formative.